Assessing the unassessed marine recreational fishery in the Eastern Cantabrian coast - Bachiller, Eneko; Korta, Maria; Mateo, Maria; Mugerza, Estanis; Zarauz, Lucia (Frontiers in Marine Science, 2022)
Within the first attempt to assess marine recreational fisheries (MRF) along the coastal villages of the Basque Country (Eastern Cantabrian Sea), off-site surveys were carried out from 2015 to 2019 to estimate captures of the main targeted species by shore fishing, boat fishing and spearfishing. Phone calls got better response rates (>50%) than email questionnaires (<25%). Spearfishing population was smaller (1000 licenses, <2% of total MRF effort) and younger, whereas boat fishers (5000 licenses, 9% MRF effort) were generally older and more experienced. Shore fishing was the most extended MRF activity (50000 licenses, 90% of MRF effort), showing wider age and experience ranges. Boat fishing targeting albacore in summer was the main MRF activity interacting with regional commercial small-scale fishery. Squids were also important for both shore and boat fishing, followed by seabass, the main target species for shore anglers. Despite surveys were primarily designed to gather information about these three species, they also evidenced, moreover with clear underestimation bias, frequent captures of generally unassessed species, such as sargo-bream (Diplodus spp.), gilthead seabream (Sparus aurata), common dentex (Dentex dentex), red mullet (Mullus surmuletus) or scorpionfish (Scorpaena spp.). Fishers with more experience, as well as spearfishers in general, captured a wider diversity of species, but individual fishers were more specialized (i.e., showing less variation between trips). Our off-site survey assessment highlights the importance of incorporating multispecies sampling schemes to develop future MRF assessment criteria, within a context of an ecosystem approach that should also consider potential interactions with commercial small-scale fishery.